Decentralized Hybrid Control for Multi-Agent Motion Planning and Coordination in Polygonal Environments*. Issue 1 (July 2017) - Sutorius, Mason; Panagou, Dimitra
Abstract: This paper presents a decentralized hybrid control scheme for the motion planning and coordination of teams of mobile agents in known obstacle environments with both convex and non-convex obstacles. A mathematical analysis using tools from switched systems theory is carried out to establish the convergence of the system trajectories under certain modeling assumptions on the surrounding environment. The design resolves a class of deadlock situations arising in earlier work, and allows for a wider class of obstacles (both convex and non-convex) to be considered in the environment. Simulation results demonstrate the efficacy of the algorithm.